1998
DOI: 10.1002/(sici)1097-4644(19980401)69:1<19::aid-jcb3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β induction of c-fos and collagenase expression in articular chondrocytes: Involvement of reactive oxygen species

Abstract: Interleukin-1 beta (IL-1) is implicated in cartilage destruction in arthritis through promotion of matrix metalloproteinase production. Upregulation of collagenase gene expression by IL-1 is known to require the transactivators Fos and Jun. Recently, reactive oxygen species (ROS) have been suggested to act as intracellular signaling molecules mediating the biological effects of cytokines. Here, we demonstrated ROS production by IL-1-stimulated bovine chondrocytes and that neutralizing ROS activity by the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 49 publications
(68 reference statements)
3
92
0
Order By: Relevance
“…Pro-inflammatory cytokines such as IL-1 induce the formation of intracellular oxidants which may function as second messengers leading to augmentation of gene expression of degradative enzymes [32]. In addition, ROS have been implicated in cartilage degeneration in OA through the initiation of chondrocyte apoptosis [33], decreased A c c e p t e d M a n u s c r i p t 15 replicative potential, catabolic changes in matrix cartilage, telomere instability and senescence [8].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines such as IL-1 induce the formation of intracellular oxidants which may function as second messengers leading to augmentation of gene expression of degradative enzymes [32]. In addition, ROS have been implicated in cartilage degeneration in OA through the initiation of chondrocyte apoptosis [33], decreased A c c e p t e d M a n u s c r i p t 15 replicative potential, catabolic changes in matrix cartilage, telomere instability and senescence [8].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, IL-1 was found to stimulate phospholipase A 2 , promoting release of arachidonic acid. Since arachidonic acid can activate NAPDH oxidase to produce superoxide, it is possible that this fatty acid may serve as an intermediate in the IL-1-induced activation of enzymes, leading to the production of ROS (Lo et al, 1998). The observations that NADPH oxidase inhibitors suppressed the IL-1b-and TNF-a-induced ROS production also indicated the involvement of NADPH oxidase in the generation of ROS induced by cytokines (Thannickal and Fanburg, 1995).…”
Section: Il-8 Expression Via Mapk and Ros In Gastric Cancer Ys Hwang mentioning
confidence: 99%
“…The oxidative stress induced by high glucose in OA and also in normal chondrocytes, although for significantly shorter periods in the later [Rosa et al, 2009], may impair normal TGF signaling and consequent responses. Indeed, increased ROS production has been shown to induce the gene expression of various MMPs in chondrocytes from different species [Lo et al, 1998;Gurjar et al, 2001]. Thus, it is possible that high glucose-induced ROS, especially in OA chondrocytes, overcome the inhibitory response induced by TGF, so that MMP-13 gene expression takes longer to be downregulated by TGF when the cells are cultured under high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, that study also showed that OA chondrocytes exposed to a high, hyperglycemia-like extracellular glucose concentration (30 mM) were unable to reduce glucose transport and GLUT-1 content which led to increased glucose accumulation and prolonged Reactive Oxygen Species (ROS) production [Rosa et al, 2009]. Increased oxidative stress has been pointed out as a major pathogenic mechanism of OA [Maneiro et al, 2003;Grishko et al, 2009], and at the cellular level, increased ROS production has been shown to mediate many catabolic responses in chondrocytes [Lo et al, 1998; Mendes et al, 2003a,b].…”
Section: Abstract: Collagen; Gene Expression; Glucose; Human Chondromentioning
confidence: 99%
See 1 more Smart Citation